A Systematic Review of Psychosocial Interventions to Cancer Caregivers - Fu, Fang; Zhao, Huaijuan; Tong, Feng; Chi, Iris (Frontiers in Psychology, 2017)
Objective: To systematically review the effect of psychosocial interventions on improving QoL, depression and anxiety of cancer caregivers. Methods: We conducted a systematic review of psychosocial interventions among adult cancer caregivers published from 2011 to 2016 . PsycINFO, PubMed, Proquest, Cochrane Library, Embase, Applied Social Sciences Index and Abstracts (ASSIA), Cumulative Index to Nursing and Allied Health Literature, Social Sciences Citation Index (SSCI) and EBSCO, China National Knowledge Infrastructure (CNKI) and WANFANG were searched. Inclusion criteria were: randomized controlled trails; psychosocial intervention to cancer caregivers; psychosocial health indicators including quality of life, depression or anxiety. Results: 21 studies out of 4666 identified abstracts met inclusion criteria, including 19 randomised controlled trails (RCTs). The intervention modes fell into the following nine categories: family connect intervention, self-determination theory-based intervention (SDT), cognitive behavioural therapy (CBT), emotion-focused therapy (EFT), comprehensive health enhancement support system (CHESS), FOCUS programme, existential behavioural therapy (EBT), telephone interpersonal counseling (TIP-C), problem-solving intervention (COPE). Conclusion: paired-intervention targeting self-care and interpersonal connections of caregivers and symptom management of patients is effective in improving quality of life and alleviating depression of cancer caregivers while music therapy is helpful for reducing anxiety of cancer caregivers .